Coordinator - Athanasiou, Androulla (My University, 2026)
We coordinated the procedure of internal and external quality control of the Language Centre. We are now working on the accreditation of our courses according to the requirements of the Cyprus Agency of Quality Assurance and Accreditation in Higher Education